2020
DOI: 10.1186/s40942-020-00259-4
|View full text |Cite
|
Sign up to set email alerts
|

25 vs. 27-gauge micro-incision vitrectomy surgery for visually significant macular membranes and full-thickness macular holes: a retrospective study

Abstract: Background To evaluate visual and safety outcomes for 25-gauge (25G) and 27-gauge (27G) micro-incision vitrectomy platforms (MIVS) for the treatment of epiretinal membrane and full-thickness macular holes. Methods Retrospective analysis of all patients who underwent internal limiting membrane (ILM) peel surgery from January 2017 through December 2018. 207 cases met the eligibility criteria for inclusion. Primary endpoint was post-operative Best-Corrected Distance Visual Acuity (BCVA) at 6 months. Results For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…A total of 1687 relevant studies were screened, of which 15 studies between 2015 and 2021, met the inclusion criteria and were involved in the meta-analysis. [9][10][11][12][13][14][15][16][17][19][20][21][22][23][24] Data obtained from these studies were shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 1687 relevant studies were screened, of which 15 studies between 2015 and 2021, met the inclusion criteria and were involved in the meta-analysis. [9][10][11][12][13][14][15][16][17][19][20][21][22][23][24] Data obtained from these studies were shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The current meta‐analysis involved 1264 subjects with the vitreoretinal disease at the baseline of the studies; 562 of them were using the 27‐gauge microincision vitrectomy surgery, and 722 were using 25‐gauge microincision vitrectomy surgery 9‐17,19‐24 . The 27‐gauge microincision vitrectomy surgery subjects had a significantly lower intraoperative and postoperative wound complication, wound suture number, and best corrected visual acuity compared with 25‐gauge microincision vitrectomy surgery in subjects with vitreoretinal disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MH is a defect in the macula that can be caused by age, trauma, or vitreoretinal disease resulting in impaired central vision, metamorphopsia, and central scotoma [ 13 ]. Currently, the standard treatment of choice for MH is vitrectomy with posterior hyaloid face (PHF) removal with ILM peeling with tamponade agent but posturing is still a debatable topic [ 14 ]. Vitrectomy can be performed using different gauge cutters.…”
Section: Discussionmentioning
confidence: 99%